Association of birth by cesarean section with academic performance and intelligence in youth: A cohort study - Agnes K. Ladelund; Julie A. Slavensky; Frederik J. Bruun; Emilie Pi Fogtmann Sejer; Erik Lykke Mortensen; Steen Ladelund; Ulrik S. Kesmodel (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction It is suggested that birth by elective cesarean section (CS) reduces the risk of birth‐related infant mortality and injury. Other studies suggest an increased risk of somatic immune‐related diseases among children born by CS such as asthma, type 1 diabetes, and inflammatory bowel disease. The WHO Statement on Cesarean Section Rates 2015 described an increase in CS globally. The statement concluded that the effects of CS on social and psychological outcomes remain unclear and that more research is needed to fully understand the effects of CS, including effects on cognition and intelligence in the child. Therefore, we aimed to investigate the association between delivery by CS (elective and acute) and school performance and intelligence in youth. Material and methods This cohort study included all Danish live‐born children in 1978–2000. We retrieved data regarding pregnancies, births, parents, school grades, and intelligence of the children from Danish registers and performed multiple imputations to avoid discarding data. The final cohort after exclusion comprised 1 408 230 children. Associations between CS and school graduation, grades, conscription attendance, and conscription intelligence scores were analyzed using univariate and multivariate logistic and linear regressions. Results Adjusted odds ratio with 95% CI of graduating from lower (LSE) and upper (USE) secondary education and of attending conscription were significantly lower in the CS group: LSE graduation: 0.87 (0.84–0.89), USE graduation: 0.93 (0.92–0.94), attending conscription: 0.95 (0.93–0.98). The CS group had significantly lower grade point averages (GPA) in LSE with adjusted differences in mean total GPA of −0.090 (−0.10 to −0.007), and mean core subject GPA of −0.098 (−0.11 to −0.08), in USE with total GPA difference of −0.091 (−0.11 to −0.075) and lower mean intelligence scores of −0.36 (−0.46 to −0.27) in adjusted linear models. A sub‐analysis revealed lower chances of graduating LSE and USE when born by acute rather than elective CS. Conclusions Chances of LSE and USE graduation and of attending conscription were significantly lower for children born by CS. However, even significant differences in mean GPAs and intelligence scores were very small, so performances when graduating school and attending conscription were comparable regardless of delivery mode.